ANTIPHYTOVIRAL ACTIVITY OF GAUPSIN BIOPREPARATION - О. I. Балко; О. А. Кіпріанова; О. Г. Коваленко; В. В. Шепелевич; Л. В. Авдєєва (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
Insectofungicidal biopreparation gaupsin inhibited for 73–100% the tobacco mosaic virus (TMV) infectivity in thornapple (Datura stramonium) and tobacco (Nicotiana tabacum) plants. The high activity of antiphytoviral substances production has been also shown by separate strains of Рseudomonas chlororaphis subsp. aureofaciens UCM В-111 and UCM В-306 – the active agents of gaupsin preparation – as well as by the thermostable water-soluble fractions isolated from their cultural fluids using sedimentation by two ethyl alcohol volumes. The latter inhibited for 86–96% infection development caused by TMV but they could not improve the plant immunity.